(untitled) (International journal of artificial intelligence, 2025)
This article confidently asserts that problem-based learning, digital literacy, statistical applications, and interdisciplinary approaches are key components in developing students' technical thinking in economics classes. It also outlines effective teaching strategies, including interactive learning, industry engagement, and competency-based assessments, while exploring their implications for economic education and employability.